Alterations of Gut Microbiome and Metabolite Profiling in Mice Infected by Schistosoma japonicum - Hu, Yue; Chen, Jiansong; Xu, Yiyue; Zhou, Hongli; Huang, Ping; Ma, Yubin; Gao, Minzhao; Cheng, Shaoyun; Zhou, Haiyun; Lv, Zhiyue (Frontiers in Immunology, 2020)
Schistosoma japonicum (S. japonicum) is one of the etiological agents of schistosomiasis, a widespread zoonotic parasitic disease. However, the mechanism of the balanced co-existence between the host immune system and S. japonicum as well as their complex interaction remains unclear. In this study, the 16S rRNA gene sequencing combined with metagenomic sequencing approach, as well as UPLC-MS metabolic profiling was applied to demonstrate changes in the gut microbiome community structure during schistosomiasis progression, the functional interactions between the gut bacteria and S. japonicum infection in BALB/c mice, and the dynamic metabolite changes of the host. The results showed that both gut microbiome and the metabolites were significantly altered in different time points after the infection. The decreases of richness and diversity as well as the differed composition of gut microbiota were observed in the infected status when compared with uninfected status. At the phylum level, the gut microbial communities in all samples were dominated by Firmicutes, Bacteroidetes, Proteobacteria and Deferribacteres; while at the genus level, Lactobacillus, Lachnospiraceae NK4A136 group, Bacteroides, Staphylococcus and Alloprevotella were the most abundant. After exposure, Roseburia and Ruminococcaceae UCG-014 decreased while Staphylococcus, Alistipes and Parabacteroides increased, which could raise the risk of infections. Furthermore, LEfSe demonstrated several bacterial taxa that could discriminate between each time point of S. japonicum infection. Besides, metagenomic analysis illuminated AMPK signaling pathway and chemokine signaling pathway were significantly perturbed after the infection. Phosphatidylcholine and colfosceril palmitate in serum as well as xanthurenic acid, naphthalenesulfonic acid and pimelylcarnitine in urine might be the metabolic biomarkers due to their promising diagnostic potential at the early stage of the infection. Also, alternations of glycerophospholipid and purine metabolism were discovered in the infection. The present study might provide further understanding of the mechanisms during schistosome infection in aspects of gut microbiome and metabolites, and facilitate the discovery of new targets for early diagnosis and prognostic. Further validations of potential biomarkers in human populations are necessary, and the exploration of interactions among S. japonicum, gut microbiome and metabolites is to be deepened in future.